Le parole e i concetti nella costruzione del curricolo verticale di chimica - Aquilini, Eleonora (Chimica nella Scuola, 2024)
The transition from common sense concepts to scientific concepts in school requires careful consideration of what and how to teach at different levels. Language must accompany the evolution of scientific concepts, so that the scientific language is not perceived as abstract and incomprehensible words. In chemistry, the word “acid” is often taken as an example of this conceptual transformation.